Students' and Teachers’ Responses to the Practice of English Medium Instruction in the Secondary School Level: Evidence from Indonesia - Nur, Maulidia Rachmawati; Nurhidayati, Nurhidayati; Saragih, Enni Erawati; Nurmayasari, Eva (Universitas Muhammadiyah Mataram, 2024)
In response to the expansion of English medium instruction (EMI) in secondary education, this qualitative case study explores students' and teachers' responses to EMI practices in the context of the secondary school level. Data for this study were collected from interview guidelines with teachers and students from a secondary school level implementing EMI, which is located in West Java Province, Indonesia. Questionnaires and interviews were used as research instruments to obtain data about students' and teachers’ responses to EMI practices. The findings showed EMI practices trigger bilingualism in the learning process. Besides, It can potentially promote students’ and teachers’ enthusiasm in the context of English for Specific Purposes in which the teacher plays an important role in the learning process. The findings also detail teachers’ knowledge of EMI, Responses to the practice of EMI, teachers’ challenges to the practice of EMI, and Students’ and Teachers’ Attitudes to the practice of EMI.